2005
DOI: 10.1029/2004wr003275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bedrock permeability on hillslope and riparian groundwater dynamics in a weathered granite catchment

Abstract: [1] To investigate the effects of bedrock permeability on the linkage between hillslope and riparian groundwater in a weathered granite headwater catchment, the groundwater dynamics were studied using intensive hydrometric and tracer observations. Water flow from the hillslope, through the hillslope/riparian interface, and into the riparian zone consists of two components: saturated through flow on the soil-bedrock interface during storms and groundwater flow within the permeable bedrock occurring year-round, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(173 citation statements)
references
References 34 publications
7
165
0
1
Order By: Relevance
“…The Kiryu Experimental Watershed is located at 34°58 0 N, 136°00 0 E, with an elevation ranging from 190 to 255 m. The mean annual air temperature from 1997 to 2002 was 13Ð9°C (Katsuyama et al, 2005). The annual precipitation, evapotranspiration, and runoff from 1997 to 2000 were 1682 mm, 792 mm, and 890 mm respectively.…”
Section: Study Sitementioning
confidence: 99%
“…The Kiryu Experimental Watershed is located at 34°58 0 N, 136°00 0 E, with an elevation ranging from 190 to 255 m. The mean annual air temperature from 1997 to 2002 was 13Ð9°C (Katsuyama et al, 2005). The annual precipitation, evapotranspiration, and runoff from 1997 to 2000 were 1682 mm, 792 mm, and 890 mm respectively.…”
Section: Study Sitementioning
confidence: 99%
“…The EG-alone-type groundwater, with very low SiO 2 concentrations, probably consisted of water flowing only through soil layers because SiO 2 is contained little in rainwater and is mainly released as solutes to subsurface water through chemical weathering processes, and the greater silica availability with increasing depth causes the subsurface water SiO 2 concentration to increase with depth [Scanlon et al, 2001]. Many previous studies conducted in granitic headwater catchments have consistently demonstrated that shallow or soil water has considerably lower SiO 2 concentrations than deep or bedrock groundwater [e.g., Shimada et al, 1992;Asano et al, 2003;Uchida et al, 2003b;Katsuyama et al, 2005]. The SiO 2 concentration of the EG-with-SPG-type groundwater at points B and D ranged between that of EG-alone-type groundwater and SPG at each point, suggesting that mixing of soil water (i.e., EG-alone-type groundwater) with bedrock groundwater (i.e., SPG) occurred at these two points when rainfall events ephemerally increased the groundwater level above the existing SPG level (i.e., EG-with-SPG-type groundwater).…”
Section: Sio 2 Concentrationsmentioning
confidence: 99%
“…[5] Hydrometric [e.g., Haria and Shand, 2004] and hydrochemical [e.g., Mulholland, 1993;Burns et al, 1998;Katsuyama et al, 2005;Soulsby et al, 2007] evidence has suggested that groundwater that has infiltrated into bedrock discharges slowly into soil layers and contributes to base flow. Runoff of bedrock groundwater often strongly influences the generation of saturated zones in soil layers.…”
Section: Introductionmentioning
confidence: 99%
“…Katsura et al [2009] reported that the hydraulic conductivity of weathered granite bedrock (10 -5 -10 -3 cm s -1 ) is higher than that of weakly weathered bedrock (10 -8 cm s -1 ) in deeper layers. Based on intensive observations of the SiO 2 concentrations of groundwater and streamwater, Katsuyama et al [2005] showed that groundwater flow within a permeable weathered granite bedrock contributed to streams year-round in one small headwater catchment. Terajima et al [1993] examined the water balance in two small catchments (0.087 and 0.255 ha) in a granitic mountain area and suggested that at least 30% and 18% of annual precipitation, respectively, percolates into bedrock.…”
Section: Introductionmentioning
confidence: 99%